Pengukuran kepuasan pelanggan dalaman bagi industri hospitaliti: kajian kes industri perhotelan di Pantai Timur Semenanjung Malaysia - Khairul Anuar Mohd Ali,; Suzyanty Mohd Shokory, (Penerbit ukm, 2009)

(untitled)
This study investigates the internal customer’s satisfaction level for the East Coast hotel industry using the SERVQUAL Model. Through SERVQUAL Model, the quality of services provided by each Human Resource Department from selected hotels are assessed by determining the expectation and perception of its internal customers. Eighty-five respondents from five different hotels have been selected in this study. A stratified random sampling method was utilised and data was collected via questionnaires. The result of the analysis show that the quality of services provided by the Human Resource Department fell short of the satisfaction level expected by its internal customers. This is demonstrated by a huge gap presence in the responsiveness dimension, which is an important dimension, based on the opinion of the internal customers. The Quality Ratio Analysis found the responsiveness dimension as the main dimension that failed to fulfil the minimum expectation of internal customers. Hence, the Human Resource Department needs to improve and prioritise further the responsiveness dimension in order to provide satisfactory service to the internal customers